The naughtiest unicorn and the school disco - O'Connell , David (London Egmont, 2021)
More hilarious adventures with Dave the naughtiest unicorn! Everyone at Unicorn School is SUPER EXCITED about the school disco! Can Mira persuade Dave to stop snacking on DOUGHNUTS, put on a GLITTERY PARTY OUTFIT and HIT THE DANCE FLOOR? The BEST DANCERS will win a special SPARKLY medal . . . and Mira is determined it will be hers! The Naughtiest Unicorn series: The Naughtiest Unicorn The Naughtiest Unicorn at Sports Day The Naughtiest Unicorn and the School Disco The Naughtiest Unicorn at Christmas
English stories
Keywords: Children's stories; Schools Juvenile fiction